TRANSESTERIFIKASI IN SITU BIJI PANDAN LAUT (Pandanus tectorius ) MENJADI BIODIESEL MENGGUNAKAN GELOMBANG ULTRASONIK - Mahlinda, M. Dani Supardan, Husni Husin, Medyan Riza (Jurnal Teknologi Industri Pertanian, 2016)
Biodiesel is a renewable, biodegradable, environmentally benign and efficient used for substitution fossil fuel. Screw pine seed (Pandanus tectorius) is one of promising material for biodiesel feedstock. The main purpose of this research was to evaluate the process production of biodiesel from screw pine seeds using ultrasound through in situ transesterification. The process was studied at reaction temperature sof 45, 55 and 65oC; reaction times of 60, 70, 80 and 90 minutes; methanol to seed ratiosof 15:1, 20:1, 25:1 and 30:1 (w/w); KOH catalyst concentrations of 3, 4, 5 and 6 (%-w of seed) for co-solvent (kloroform) to seed ratio of 1:1 (w/w). The experimental results showed that the maximum yield of biodiesel obtained was 86.38% at reaction temperature of 65°C, mass ratio of methanol to seed 25:1 (w/w), 5% of KOH as catalyst and 80 minutes of reaction time. Test results of physicochemical properties showed that viscosity, density and acid value conformed to the SNI 7182-2012 standard. Gas Chomatography-Mass Spectrometry analysis showed that biodiesel consisted of five fatty acid methyl esters of methyl octadec, methyl linoleate, methyl palmitate, methyl stearate and methyl oleate.Keywords: biodiesel, in situ transesterification, screw pine, ultrasound